1893 Fla. Laws 71 - (:unkn) unknown (My University, 1893)
Ch. 4147: Required a license to carry a Winchester or other repeating rifle. Licenses to cost a one hundred dollar bond. Violators shall be guilty of a misdemeanor and a fine not exceeding one hundred dollars or sixty days in jail.
Keywords: CARRY